Emigration und Modernisierung Deutschlandsaufenthalte der ungarischen Elite im 19. Jh.: Der Fall József Eötvös - Gángó, Gábor (Contingentia, 2009)
The study offers a comprehensive overview on the works and activity of József Eötvös, central personality of the 19th-century modernisation of political culture and educational system in Hungary. It also reveals the paradoxical consequences of his efforts, namely the fact that while the first and second generation of Hungarian intellectuals returning home from Germany in the early ’40s and after the Austro-Hungarian Compromise in 1867 successfully contributed to the building of the modern cultural nation, at the end of the century the generation of émigrés chose Germany on purpose to escape the nationalistic institutional framework of Hungarian culture and sciences.